Postprandial hyperglycemia in patients with noninsulin-dependent diabetes mellitus. Role of hepatic and extrahepatic tissues. - Firth, R G (1986)
Patients with noninsulin-dependent diabetes mellitus (NIDDM) have both preprandial and postprandial hyperglycemia. To determine the mechanism responsible for the postprandial hyperglycemia, insulin secretion, insulin action, and the pattern of carbohydrate metabolism after glucose ingestion were assessed in patients with NIDDM and in matched nondiabetic subjects using the dual isotope and forearm catheterization techniques. Prior to meal ingestion, hepatic glucose release was increased (P less than 0.001) in the diabetic patients measured using [2-3H] or [3-3H] glucose. After meal ingestion, patients with NIDDM had excessive rates of systemic glucose entry (1,316 +/- 56 vs. 1,018 +/- 65 mg/kg X 7 h, P less than 0.01), primarily owing to a failure to suppress adequately endogenous glucose release (680 +/- 50 vs. 470 +/- 32 mg/kg X 7 h, P less than 0.01) from its high preprandial level. Despite impaired suppression of endogenous glucose production during a hyperinsulinemic glucose clamp (P less than 0.001) and decreased postprandial C-peptide response (P less than 0.05) in NIDDM, percent suppression of hepatic glucose release after oral glucose was comparable in the diabetic and nondiabetic subjects (45 +/- 3 vs. 39 +/- 2%). Although new glucose formation from meal-derived three-carbon precursors (53 +/- 3 vs. 40 +/- 7 mg/kg X 7 h, P less than 0.05) was greater in the diabetic patients, it accounted for only a minor part of this excessive postprandial hepatic glucose release. Postprandial hyperglycemia was exacerbated by the lack of an appropriate increase in glucose uptake whether measured isotopically or by forearm glucose uptake. Thus as has been proposed for fasting hyperglycemia, excessive hepatic glucose release and impaired glucose uptake are involved in the pathogenesis of postprandial hyperglycemia in patients with NIDDM.